Predicting variations in the areas of circular leaks in water pipes due to changes in pressure - Nsanzubuhoro, Rene Mathias Nsanzintore (Department of Civil Engineering, 2017)
Leak openings in water distribution system pipes are not static, but have areas that vary with pressure. These changes in area affect the way that leakage respond to changes in pressure, and was thus important for municipal engineers to understand. This study focussed on round hole leak openings that can exist as pipe failures. In this study, a finite element analysis (FEA) study was carried out to model the behaviour of round holes in pipes with varying pressure under elastic conditions. It was found that the areas of the holes vary as linear functions of pressure in the pipe. The slope of this linear function, also referred to as the head-area slope m, was identified as a critical element to investigate because this head-area slope essentially gives an indication of the extent to which the leak area is sensitive to pressure. The FEA was then used to better understand the factors that affect the head-area slope m. In order to understand which parameters affect the head-area slope m, a parametric study was conducted. This parametric study was done by varying each parameter in turn to study the effect of that parameter on the head-area slope of the pipe. The parameters investigated in the study include the pipe material (elastic modulus, Poisson's ratio and longitudinal stress), pipe geometry (wall thickness and internal diameter) and hole diameter. It was found in this study that of the five aforementioned geometric and material parameters, the elastic modulus, wall thickness and internal diameter had the most significant effect on the head-area slope m. The extent to which these parameters influenced m depended on the hole diameter. It was found that as the hole diameter increased the effect of the parameter was more significant. Solid mechanics theory was then used to develop an equation to predict the head-area slope of round holes in different pipes and materials. Various techniques were used in the development of the equation. To calibrate and validate this equation the head-area slopes calculated from the equation were compared and plotted against the finite element head-area slopes. A reasonable expression was found that can be used in further research and practice. The head-area slopes m obtained from this equation was compared to the head-area slopes m obtained in the FEA analysis. It was found that this expression predicts the finite element model analysis reasonably well, producing trends that are similar to those found from the finite element models.